Makna Kepastian Hukum dalam Perspektif Filsafat Hukum dan Implementasinya di Indonesia - Deandra Tiffany; Natalia Emanuela Tingginehe; Eben Haezer Willem Putrayasa; Gracia Cindy Stefani; Caroline Debora (Jurnal Ragam Pengabdian, 2026)
Legal certainty is a fundamental pillar of the rule of law, functioning to ensure order, justice, and protection within society. However, in practice, legal certainty often faces challenges due to the gap between written legal norms and their implementation. This study aims to analyze the meaning of legal certainty from a philosophical perspective of law and to examine its implementation within the Indonesian legal system. The research employs a normative juridical method with statutory, conceptual, and philosophical approaches, utilizing primary and secondary legal materials analyzed through descriptive-analytical and argumentative techniques. The findings indicate that legal certainty cannot be narrowly understood as merely written rules, but must be closely related to the values of justice and utility. In the Indonesian context, the implementation of legal certainty still encounters various obstacles, such as overlapping regulations, inconsistent court decisions, and weak integrity of law enforcement officials. Therefore, comprehensive legal reforms are necessary to achieve legal certainty that is both just and beneficial to society.